2018
DOI: 10.1021/acs.joc.8b00270
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Explosion Hazards of 4-Azido-l-phenylalanine

Abstract: A reliable, scalable, cost-effective, and chromatography-free synthesis of 4-azido-L-phenylalanine beginning from L-phenylalanine is described. Investigations into the safety of the synthesis reveal that the Ullman-like Cu(I)-catalyzed azidation step does not represent a significant risk. The isolated 4-azido-L-phenylalanine product, however, exhibits previously undocumented explosive characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…We also incorporated an iodine atom in N -Me- d -Phe 1 to give N -methyl- p -iodo- d -phenylalanine ( N -Me- d -Phe I 1 ), to permit determination of the X-ray crystallographic phases. 15,16 Figure 1 illustrates the structure of the resulting teixobactin analogue 3 , a homologue of Lys 10 -teixobactin ( 2 ). Teixobactin analogue 3 does not form a gel and exhibits only modest activity against S. aureus (MIC=16 μg/mL).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also incorporated an iodine atom in N -Me- d -Phe 1 to give N -methyl- p -iodo- d -phenylalanine ( N -Me- d -Phe I 1 ), to permit determination of the X-ray crystallographic phases. 15,16 Figure 1 illustrates the structure of the resulting teixobactin analogue 3 , a homologue of Lys 10 -teixobactin ( 2 ). Teixobactin analogue 3 does not form a gel and exhibits only modest activity against S. aureus (MIC=16 μg/mL).…”
mentioning
confidence: 99%
“…We postulated that N -methylation of the peptide backbone would attenuate the aggregation and permit the growth of crystals. , We discovered that N -methylation of d -Gln 4 indeed facilitated crystallization. We also incorporated an iodine atom in N -Me- d -Phe 1 to give N -methyl- p -iodo- d -phenylalanine ( N -Me- d -Phe I 1 ), to permit determination of the X-ray crystallographic phases. , Figure illustrates the structure of the resulting teixobactin analogue 3 , a homologue of Lys 10 -teixobactin ( 2 ). Teixobactin analogue 3 does not form a gel and exhibits only modest activity against S.…”
mentioning
confidence: 99%
“…The cost of pAzF is considerable for large-scale production of nanobodies but it can be produced in-lab in few steps from inexpensive commercially available starting materials. In this study, pAzF was synthesized in-house following the detailed protocol reported by Gregory A. Weiss and co-workers [ 21 ]. The method is scalable to at least 50 g starting material.…”
Section: Methodsmentioning
confidence: 99%
“…Process safety scientists in the pharmaceutical industry are chemists and engineers who dedicate themselves to identify and minimize potential risks associated with thermally unstable materials, combustible dusts, and runaway reactions from R&D laboratories to manufacturing facilities. Numerous publications illustrate such work accomplished by process safety scientists. For example, Tian et al evaluated thermal safety on a hydroamination reaction using DMSO as solvent, studied the potential autocatalytic decomposition with DMSO, and successfully launched the process for commercial production safely.…”
Section: Process Safety In the Pharmaceutical Industrymentioning
confidence: 99%